Characterization of chitosan-ferulic acid conjugates and their application in the design of β-carotene bilayer emulsions with propylene glycol alginate. (July 2018) - Wang, Di; Mao, Like; Dai, Lei; Yuan, Fang; Gao, Yanxiang
Abstract: The current study investigated the formation of chitosan-ferulic acid (FA) conjugates (CFC), and the application of CFC and propylene glycol alginate (PGA) in designing β-carotene bilayer emulsions. CFC was synthesized based on the carbodiimide-mediated coupling reaction, which was confirmed by FITR and 1 H NMR analysis. The resulting CFC could have a high ratio of FA grafted onto chitosan (83.20 ± 0.81 mg/g) and exhibited stronger antioxidant activity than FA, and better water solubility than chitosan alone. Being oppositely charged, PGA and CFC formed bilayer interface covering the oil droplets of β-carotene emulsions through electrostatic attraction. The results showed that the concentration of CFC affected the interfacial content of FA, particle size, and surface charge of the droplets in β-carotene emulsions. Compared to chitosan or chitosan-FA mixture (CFM) stabilized bilayer emulsions with PGA, CFC stabilized bilayer emulsions showed better creaming stability against different environmental stresses (i.e., pH, heat and ionic strength) and higher β-carotene stability when exposed to thermal treatment and UV light. The knowledge obtained in the present study could be useful in designing bilayer emulsions for bioactive compounds with improved performance. Graphical abstract: Image Highlights: Chitosan-ferulic acid conjugates (CFC) were synthesized and characterized. CFC have higher antioxidant activity and water solubility. Bilayer emulsions were fabricated with CFC and propylene glycol alginate. Bilayer emulsions exhibited improved stability against adverse conditions. β-Carotene had improved stability in bilayer emulsions.